Social and Economic Determination of Agroforestry Farmer's Income in Karang Sidemen Village, Rarung Forest Area - Pande Komang Suparyana; Rifany Nur Sindy Setiawan; Addinul Yakin; Amiruddin; Halimatus Sa’diyah; M. Fahed Ramadhan (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
Karang Sidemen Village is located in North Batukliang District, Central Lombok Regency. This village is situated in a strategic location, surrounded by productive forests and fertile agricultural land. A deep understanding of the conditions in this village is expected to provide a valuable contribution to the formulation of sustainable development policies and programs while supporting environmental sustainability in the area. Multiple linear regression analysis is used as a calculation tool to analyze this study because in this study, there is one dependent variable, namely the income of agroforestry farmers, and there are five independent variables, namely the level of formal education, agroforestry farming experience, number of family dependents, land area and motivation for agroforestry farming. This research was conducted in Karang Sidemen Village, North Batukliang District, Central Lombok Regency, West Nusa Tenggara Province at the Mitra Farmer Group in the Rarung Forest Area. The research was carried out from April to September 2024. The number of samples taken was 70 respondent farmers. Overall, the regression model used is quite good and significant in explaining the influence of social and economic factors on the income of agroforestry farmers. Farmer motivation plays a vital role in the success of agroforestry efforts. Therefore, programs that increase farmer motivation, such as providing incentives, awards for high-achieving farmers, or intensive mentoring, can be implemented to encourage farmer work enthusiasm and innovation.